1980
DOI: 10.1177/073088848000700405
|View full text |Cite
|
Sign up to set email alerts
|

Waitressing, Vulnerability, and Job Autonomy

Abstract: The question for research is: what effect does job autonomy have on the sense of vulnerability expressed by those working for tips rather than for contracted wages? Vulnerability, the dependent variable, is a measure of the worker's perception of risk attached to working under such an arrangement. Autonomy, the independent variable, evaluates organizational conditions which permit or limit control over one's work. It is measured by restaurant procedures of surveillance and discipline. Sixty-one waitresses empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…However, owing to the voluntary nature of tipping, extending such trust does not ensure that the customer will leave an adequate tip nor does it alleviate the potential of being 'stiffed' (Paules, 1991). Thus, the uncertainty inherent in the institution of tipping causes servers to feel a sense of powerlessness over their wage security (Butler & Skipper, 1980). Consistent with this finding, the majority of servers in New Zealand, where tipping has not yet been institutionalized, report that 'they appreciate the financial benefits of tips, but they prefer wage certainty to the unpredictability of a tip-dependent income' (Casey, 2001, p. 25).…”
Section: An Alternative Explanatory Framework For Race-based Tipping supporting
confidence: 58%
“…However, owing to the voluntary nature of tipping, extending such trust does not ensure that the customer will leave an adequate tip nor does it alleviate the potential of being 'stiffed' (Paules, 1991). Thus, the uncertainty inherent in the institution of tipping causes servers to feel a sense of powerlessness over their wage security (Butler & Skipper, 1980). Consistent with this finding, the majority of servers in New Zealand, where tipping has not yet been institutionalized, report that 'they appreciate the financial benefits of tips, but they prefer wage certainty to the unpredictability of a tip-dependent income' (Casey, 2001, p. 25).…”
Section: An Alternative Explanatory Framework For Race-based Tipping supporting
confidence: 58%
“…As such, compensation via tips motivates employees to discriminate against customers perceived to be poor tippers, which can lead to lawsuits and the loss of business from those customers discriminated against (Lynn 2004). Third, tipping results in variable and uncertain incomes (Butler and Skipper 1980). This uncertainly is likely to attract a younger, part-time, and less professional workforce (Parise 1987).…”
Section: Voluntary Tipping and The Selective Attraction And Retentionmentioning
confidence: 99%
“…In response to the inherent uncertainty and exploitive nature of this system of labour, researchers have found that service industry workers use the resources at their disposal to maximize earnings and their sense of control in the workplace. In particular, they engage in "emotional labour" (Hochschild, 1983) and promotional activities in an effort to: sell more food and drinks, increase earnings, have greater control over the reward structure (Butler and Snizek, 1976;Butler and Skipper, 1980;Paules, 1991;Sallaz, 2002) and enhance their sense of autonomy (Paules, 1991;Sallaz, 2002). According to Paules (1991), the focus of workers is their own interests, with the businesses' interests and house rules given secondary consideration-typically, when they fit with their own interests.…”
Section: Literature and Frameworkmentioning
confidence: 99%
“…Despite feeling varying degrees of commitment to, and constraint imposed by, the workplace, most club staff we spoke with felt that the structural organization of the strip club put them all in a similar economic position (see Bruckert, 2002): one lacking in the certainty and security that accompanies a salaried or set wage contract with an employer (Butler and Skipper, 1980). Similar to workers in other parts of the service industry (Paules, 1991;Sallaz, 2002), they engage in a range of independent and collective resistance strategies in order to enhance their sense of autonomy and economic security.…”
Section: The Social Organization Of the Strip Clubmentioning
confidence: 99%